KNOWLEDGE AND PERCEPTION OF ECONOMICS STUDENTS ON IMPLEMENTING FINTECH IN THE DIGITAL ERA (Case Study of Islamic Economics Students at the State Islamic University of North Sumatra) - Yuannisa, Rizka Adlia; Ridwan, Muhammad; Arif, muhammad (Universitas Muhammadiyah Sumatera Utara, 2023)
Rizka Adlia Yuannisa's research (2022) entitled,